Estrogenic hazards of short chain phthalates and bisphenols found in cosmetic products - Chebbi, Manel; Beltifa, Asma; Alibi, Sana; Di Bella, Giuseppa; Loturco, Vincenzo; Sire, Olivier; Ben Mansour, Hedi; Le Tilly, Véronique (International journal of environmental health research, 2022)
For several years, environmental exogenous agents, called endocrine disruptors, are suspected to interfere with the essential functions of reproduction and development in many living organisms. In this study, endocrine disruptors including five phthalates and two bisphenols contents in finished products were assayed and their estrogenic activity were measured by using the Yeast Estrogen Screen system with respect to human and trout estrogen receptors hERα and rtER S . Independently of the estrogen receptor, only short-chain phthalates (DBP and BBP) and the two bisphenols exhibited an estrogenic activity. Besides, the risk of three end-products (agro-food, cosmetics, and pharmaceutical) was evaluated before and after forced aging. Only two cosmetics the face cream and the perfume presented a hazard which increases with aging. These results are consistent with the compounds identified by Gas chromatography-mass spectrometry. These findings confirmed that the YES system can be routinely used to evaluate the estrogenic hazards within finished products.